Team Games Tournament Model in Elementary School Students: Learning Outcomes of Passing in Football Games - Suryansyah, Suryansyah; Badaru, Benny; Bustang, Bustang; Hasyim, Hasyim; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study goal is efforts to improve passing learning outcomes in football games through the Teams Games Tournament (TGT) model for elementary school students. This type of research is classroom action research (CAR). This research was conducted in Grade VI. The study involved a student from Islamic Elementary School Minasa Upa, with a sample consisting of 24 individuals. The data collection technique used the basic locomotor movement test. The findings of the study indicate that in cycle I, the passing learning outcomes for grade VI were assessed. The students of Islamic Elementary School Minasa Upa Makassar were 13 students (46%) on a complete scale and 11 students (54%) on an incomplete scale. While there were 20, or 83%, of students in the minimum completion criteria (complete) category, those who did not complete were 4, or 17%, of students out of 24 students in total. At the second meeting of cycle II, it was found that 83% of the students, or 20 out of 24, achieved a score of ≥ 75. This indicates a significant increase in learning outcomes for passing the ball using the Teams Games Tournament model in the soccer game for class V. The study was conducted at an Islamic elementary school located in Minasa Upa.